HUBUNGAN PERAN IBU DENGAN PERKEMBANGAN MOTORIK KASAR DAN HALUS USIA 3 TAHUN DI PAUD IMELDA - Silalahi, Bernita (Jurnal Keperawatan Priority, 2020)
Growth at gross motoric, fine motoric the child 3 year can be told golden year. Hand in glove it’s bearing with the mother role in stimulus each; every its chid growth phase. Child growths at the age have to always watch seriously from parent especially mother. If there were any growth delay of child not is immediatelya inspection hence delay of the child can become something serious matter till child grew sup. This research aim toto analyse the relation of role mother with gross motoric, fine motoric the child 3 year. Desain Research used is reseach of survey by using approach of cross sectional, the population is mother and child 3 year in PAUD Imelda Medan a number 30 people with the amount sampel 30 people by using saturated sampling. Independen variable is role mother and variable dependen is growth gross motoric, fine motoric. Measuring instrument of kuesioner and data processingly is editing, coding, scoring, tabulating. The analyse data was by using test of rank spearman. The result this study is p values ​​= 0.906 (<0.05) were obtained there is a relationship between the role of the mother with the development of gross motor and fine motor skills of children aged 3 years. Suggestion parents continue to improve and carry out their role even though they have to work to support the family economy so that children can develop properly.